2020
DOI: 10.1038/s41598-020-59011-5
|View full text |Cite|
|
Sign up to set email alerts
|

The Dopamine D5 receptor contributes to activation of cholinergic interneurons during L-DOPA induced dyskinesia

Abstract: The dopamine D5 receptor (D5R) is a Gα s-coupled dopamine receptor belonging to the dopamine D1-like receptor family. Together with the dopamine D2 receptor it is highly expressed in striatal cholinergic interneurons and therefore is poised to be a positive regulator of cholinergic activity in response to L-DOPA in the dopamine-depleted parkinsonian brain. Tonically active cholinergic interneurons become dysregulated during chronic L-DOPA administration and participate in the expression of L-DOPA induced dyski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 64 publications
0
21
2
Order By: Relevance
“…Alternatively, the observed effects could be due to ligand‐independent D1/D5 receptor activity. The D5R has high constitutive activity, 36,37 and a recent study suggested that its expression is increased in striatal tissue from dyskinetic mice 38 . Because constitutive activity relates to levels of D5R expression and may result in a time‐dependent accumulation of intracellular cAMP, 37 we tested the effects of an inhibitor of the cAMP cascade, Rp‐cAMPS, on SCINs from dyskinetic mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, the observed effects could be due to ligand‐independent D1/D5 receptor activity. The D5R has high constitutive activity, 36,37 and a recent study suggested that its expression is increased in striatal tissue from dyskinetic mice 38 . Because constitutive activity relates to levels of D5R expression and may result in a time‐dependent accumulation of intracellular cAMP, 37 we tested the effects of an inhibitor of the cAMP cascade, Rp‐cAMPS, on SCINs from dyskinetic mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Decreasing the striatal levels of Ras-guanine nucleotide-releasing factor (Ras-GFR1) leads to inhibition of the Ras/ERK pathway in parkinsonian mice. Ras-GFR1 affects the Ras-ERK pathway only in dSPNs, without affecting the cholinergic interneurons of ChIs [ 80 ]. It, therefore, affects specific downstream D1R pathways, consequently inhibiting the development of hypersensitivity to DA stimulation in the neurons.…”
Section: Resultsmentioning
confidence: 99%
“…It, therefore, affects specific downstream D1R pathways, consequently inhibiting the development of hypersensitivity to DA stimulation in the neurons. This is associated with LID developing less, although dopaminergic stimulation retains its therapeutic effect on parkinsonian motor symptoms [ 80 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…The AIM scores from four subtypes were summed for each time point. The ALO score (sum of the axial, limb, and orofacial scores) is more responsive to human dyskinesia than are locomotive scores ( Castello et al, 2020 ). Therefore, the ALO score was also analyzed in this study.…”
Section: Methodsmentioning
confidence: 99%